Etude Des Anomalies De Résistivités Pour L’optimisation Des Implantations De Forages D’hydraulique Villageoise En Milieu De Socle: Cas De La Région Du Haut-Sassandra (Centre-Ouest De La Côte d’Ivoire) - Kouassi Kouamé Auguste; Kouassi Francis Williams; Kouadio Zilé Alex; Ballo Bi Herber Esaïe; Coulibaly Adama, A.; Kamagaté Bamory (European Scientific Journal, ESJ, 2018)
Effective groundwater collecting in the basement requires characterization and identification of the productive aquifer systems that are developed there. Therefore, our study relates to the identification, analysis and description of success indicators of geophysical implantations. It about the type and form of anomaly and the type of survey curve. These indicators are obtained following interpretation of trainings and electrical soundings data. A statistical analysis of these indicators is done using the crosstab method. This reveals that drilling productivity is influenced by indicators mentioned above. Indeed, the combination of type A or H soundings obtained straight up CCL type and W or U form anomalies has the best results of up to 100% success rate. The flow rates obtained are generally large (Q> 4 m3 /h). On the other hand, drilling implanted from a type A sounding on a U or V form anomaly and CCE type has high failure rates (33% to 60%).